Clinical features and outcomes in 154 patients with haemorrhagic moyamoya disease: comparison of conservative treatment and surgical revascularization. (October 2015) - Huang, Zheng; Ding, Xuehu; Men, Weidong; Zhang, Dong; Zhao, Yuanli; Wang, Rong; Wang, Shuo; Zhao, Jizong
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Rebleeding is an unsatisfactory outcome for patients with haemorrhagic MMD. This study mainly investigated clinical features and outcomes in haemorrhagic MMD. Methods: A retrospective review was performed on a total of 154 patients with haemorrhagic MMD comprising 126 surgically treated and 28 conservatively treated patients. Results: There were 102 female and 52 male patients with a mean age at the initial bleeding of 33.95 years. Preoperative rebleeding occurred in 37 patients, and multivariate Cox regression analysis demonstrated that age at the time of initial bleeding (P < 0.001, HR = 1.093) was a risk factor for preoperative rebleeding. Of 124 patients with surgical revascularization, perioperative ischaemic stroke occurred in five (4.03%) and intracranial bleeding in four (3.23%). The mean follow-up period was 36.12 months. Recurrent bleeding occurred in six (10.17%) of 59 patients treated with direct revascularization, seven (20.69%) of 34 patients treated with indirect revascularization, two (6.45%) of 31 patients treated with combined revascularization and six (21.43%) of 28 patients treated conservatively. Kaplan–Meier analysis revealed no statistical differences in preventing rebleeding between direct, indirect and combined revascularization and conservative treatment (P = 0.311). Conclusions: Age at the initial bleeding is a risk factor for rebleeding in haemorrhagic MMD. Although surgical revascularization show the tendency to decrease the rebleeding rate, there is no statistical difference between direct revascularization, indirect revascularization, combined revascularization and conservative treatment in preventing rebleeding. Further study is needed to determine whether surgical revascularization is effective in select population or with certain techniques.